THE PORTAL CRANES WITH TANDEM SPREADERS AND THEIR COST ADVANTAGES (Perner's Contacts, 2011)
This paper deals with new system of reloading of container portal cranes in container terminals. For industry-leading terminals that seek to turn container ships as rapidly as possible, the Tandem spreader offers dynamic and unmatched loading and unloading capacity. The Tandem spreader has the capacity and the flexibility to handle all possible combinations of 20 foot, 40 foot, and 45 foot containers both quickly and efficiently. It can also handle four 20 foot containers simultaneously and seperate the two 20 foot containers longitudinally between 0 and 1,5 metres.
Keywords: spreader; tandem; portal crane; container; reload